In Situ Microwave Synthesis of SnO2‐Porous Biomass Carbon as Anode Materials for Lithium‐Ion Batteries. Issue 10 (3rd June 2021) - Gong, Keyu; Ma, Yiman; Zhang, Tao; Yan, Lei; Miao, Yang; Gao, Feng
Abstract : Using absorbent cotton fiber as raw material, the porous biomass carbon (PC) structure is obtained by the Mg 2+ template method. Then, SnO2 particles are loaded on the surface and internal pores by microwave treatment to obtain a composite material as anode material for lithium ion batteries, which releases a stable capacity of 508 mAh g −1 after 300 cycles at a current density of 300 mA g −1 . The PC structure not only offers a large specific surface area and active sites, but also buffers the expansion and agglomeration of the SnO2 particles during the deintercalation of lithium ions. Abstract : Using absorbent cotton fiber as raw material, the porous biomass carbon structure is obtained by the Mg 2+ template method. Then, SnO2 particles are loaded on the surface and internal pores through microwave treatment to obtain SnO2 @single‐walled nanotubes, which releases a stable capacity of 508 mAh g −1 after 300 cycles at a current density of 300 mA g −1 .